Online Course Tailoring Design through Project-Based Learning Syntax in Fashion Studies - Rahmasari, Anggraeni; Situmorang, Robinson; Kustandi, Cecep (CV. Media Digital Publikasi Indonesia, 2024)
In learning Tailoring courses, understanding theory is a very important basis before students practice. Without a strong understanding of theory, tailoring practice will only be trial and error. Therefore, lecturers must ensure that each student really masters the basic concepts before stepping into the practical stage. This study aims to analyse the needs of fashion students in online-based tailoring learning. This research collaborates with 10 students who have taken tailoring courses and 10 students of class 2024. Participants in this study also involved tailoring lecturers. Data collection techniques were conducted through in-depth interviews, participatory observation and documentation. The results of this study show that online courses can bring success to student learning, making it more interesting and stimulating. Online courses also make it possible to replay materials anytime and anywhere, minimising misunderstandings and ambiguities. The development of online learning in Tailoring course will be done by using Moodle as a learning management system by applying Project Based Learning approach